Efforts to Prevent and Control Tuberculosis Transmission Among Household Contacts: TB Prevention in Household Contacts - Elsje. I. Tetelepta; Harianti Fajar (CV. Paperhome Indonesia, 2025)
Tuberculosis (TB) remains a major public health concern in Indonesia, particularly among household contacts of pulmonary TB patients. This community outreach initiative was conducted in Amantelu Subdistrict, Sirimau District, Ambon City, with the objective of reducing TB transmission through targeted interventions. The program involved door-to-door health education, distribution of educational materials (posters and leaflets), and sputum sample collection from household contacts. The educational materials emphasized Clean and Healthy Living Behavior (PHBS) as a strategy to prevent TB transmission. Based on field data, 9 suspected TB cases were identified in December 2024, with a contact screening coverage rate of 52.5%. Key barriers included low public awareness and insufficient collaboration between health workers and families. The program demonstrated that continuous health education and proper environmental conditions, such as ventilation and hygiene, are critical in TB prevention. Strengthening interpersonal communication between healthcare providers and communities is essential for improving TB control outcomes, especially in the post-pandemic era.